Concentration of salivary cortisol and testosterone in elite women football players: analysis of performance in official matches - Casanova, N. R.; Travassos, B. R.; Ferreira, S. F.; Garrido, N. D.; Costa, A. M. (Kinesiology, 2020)
This study aims to evaluate the relation between salivary concentrations of cortisol (C), testosterone (T), the ratio T:C and the individual performance of top-level female soccer athletes during official matches. Eighteen female athletes from a national soccer team (age 23.06 ± 4.33 years) participated in the study. Four official matches were analysed and the on-field time of each player as well as the index of individual effectiveness were calculated. Players were classified in two clusters according to their individual performance (cluster 1 - poor individual performance; cluster 2 - good individual performance) using K-means and their hormonal variables were compared. The players of cluster 2 generally revealed higher values (p <.05) in both the positive actions and individual effectiveness, when compared with the players of cluster 1. The players of both clusters presented identical values of C, T and T:C at the four evaluated matches. The athletes of cluster 2 showed a significant increase in C (p <.05) and a significant decrease in T and T:C before the games lost (M2 and M5). However, there was no linear relation between the variation of both hormones during the matches and the individual performance of players. Performance in competition revealed significant differences between players, though with no apparent relation to the hormonal kinetics of C and T before and after the matches.